FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK KESEHATAN REPRODUKSI PADA SISWA PUTRI DI SD ISLAM HIDAYATULLAH SEMARANG - Della Zulfa Rifda; Besar Tirto Husodo; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Currently Indonesia is in emergency situations of sexual violence, coupled with the high reproductive problems especially on female. One of the reaseon is the low reproductive health education on children in Indonesia. Reproductive health education in Hidayatullah Primary School has not according with the curriculum that being used. This research aims to analyze any factors relating to the reproductive health practice on female students in Hidayatullah.This research is a quantitative with cross sectional approach. Using total sampling on all of female students (49 students) on 6th grade in Hidayatullah. The data was collected by interview using a questionnaire. This research use univariate and bivariate analysis.The research showed that the most respondents are 12 years old (51%) and already puberty (59,2%). Most of the respondents have a good reproductive health practices (51%). The chi-square test showed that attitudes about reproductive health practice (p=0,007) and the infrastructure that support practice of reproductive health (p=0,009) are significantly related to reproductive health practices. While the variables of puberty (p=0,644), knowledge (p=0,889), methodes of education (p=0,644) teacher’s role (p=0,146), parent’s role (p=0,84) are not significantly related to reproductive health practice of female students in Hidayatullah.The research concluded the importance of the role of school in providing reproductive health education at an early age. This research recommended to increase the knowledge of children about reproductive health, support infrastructure of school about reproductive organs needed, modify the method of reproduction health education, and optimize the role of teacher as counselors about reproductive organs.